(untitled) (Istituto Lombardo - Accademia di Scienze e Lettere • Rendiconti di Lettere, 2021)
The book Riflessioni interdisciplinari per un dibattito contemporaneo su violenza, ordine, sicurezza offers an interesting interdisciplinary perspective on aspects of the social life that undoubtedly show continuity between past and present and that exert a strong influence on criminal systems. If fear, as an instinct, constitutes a natural defense tool for the individual, ‘collective’ fear is a phenomenon open to different declinations, not all positive, as we will see, for example, in the current hypertrophy of the criminal law. Sometimes collective fear is triggered by objective causes (e.g. by natural catastrophes, epidemics, famines, wars or revolutions); sometimes, instead, collective fear is generated by the so called ‘culture of fear’. Such culture instills and amplifies a sense of insecurity towards true or presumed enemies by using propaganda, rhetoric or violence (just think at the ‘function’ of terrorism). This insecurity, in turn, drives people to search safety and strengthens the power of those who offer protection even with the tools of the criminal law.